Firm Size Sebagai Salah Satu Penentu Firm Performance - Muhammad Saifi; Intan Lifinda Ayuning Putri; Langgeng Setyono; Kemal Sandi; Lusi Kurnia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This article examines the contribution of firm size as a determinant of firm performance. The novelty of the research is to develop a new model related to the determinants of firm performance, especially the firm size variable. Another novelty in this study is that it is more comprehensive in seeing the effect of investment opportunity set, capital structure, and dividend policy on company performance and dividend policy, as well as company size as a moderating variable. The number of samples is 26 companies with a period of 5 years, 2018-2022. Research hypothesis testing using Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that investment opportunity set has a significant effect on dividend policy, capital structure has a significant effect on dividend policy, investment opportunity set has no significant effect on company performance, capital structure has no significant effect on company performance, dividend policy has a significant effect on dividend policy. Dividend policy has a significant effect on firm performance, firm size significantly moderates the effect of investment opportunity set on dividend policy, firm size does not significantly moderate the effect of capital structure on dividend policy, investment opportunity set has a significant effect on firm performance through dividend policy, capital structure has a significant effect on firm performance through dividend policy. Keywords: Investment Opportunity Set, Company Size, Dividend Policy, Company Performance